Значення та роль держави в сфері правотворчої діяльності в сучасних умовах: постановка проблеми - Дідич, Т.О. (Альманах права, 2012)
В статті проведено аналіз поглядів вчених щодо розуміння правотворчої діяльності як предмету діяльності держави в особі її органів, розкрито роль держави у здійсненні правотворчості в сучасних умовах розвитку правової системи. В статье проанализированы идеи ученых в сфере правотворческой деятельности государства в лице его органов, раскрывается роль государства как субъекта правотворчества в современных условиях развития правовой системы. It is given the analysis of approaches onto understanding of law-making activity as activity of the state through its bodies. It is exposed the role of state in feasible law-making in modern terms of the legal system. Legislative activity is complex and multifaceted. It provides the formation of rules of national and international law. At the same time law-making activity is a kind of legal practice as a result we receive adoption of legal acts. The author reconsidered the state’s role in law-making in terms of understanding the state and power of legislative activity as a complex phenomenon. This understanding of law-making reflects the democratic nature of the state, a high level of civil society that allows combining state and power work in law-making and law-making activities of civil society actors and the international community. In modern conditions of democratization in Ukraine the development of state and civil society is focus on scientific community. Hence, we should not forget about law-making activities of the state as a central law-making entity that provides formation of national legislation and direct impact onto international lawmaking by implementing national interests.